THE EFFECT OF SERVICE QUALITY ELEMENTS ON CUSTOMER SATISFACTION AT BRI UNIT UNSRAT MANADO - Marselin Binowo; Frederik G. Worang; Fitty V. Arie (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
The development of services at banking sector companies in Indonesia has been increasing from year to year. This can be seen from the existence of intense competition between banks in Indonesia. Along with this fierce competition, banks are required to maintain the quality of their service. Banks must provide good quality services to their customers, as a benchmark that distinguishes the bank from its competitors, because customers will always looking for bank that can provide the good service that align with their expectations and desires. In the banking industry, customer satisfaction become one of the factors or indicators which proves that the bank has been able to compete in providing excellent service to their customer. The field of service company that will be examined in this study is a service company in the banking sector, which is BRI Unit Unsrat Manado. This research has purpose to analyze and to find out the real evidence of the effect of service quality elements (SERVQUAL) on customer satisfaction. The sample of this research is 50 respondents which are the loan customers/debtors of BRI Unit Unsrat. Data analysis used Multiple Linear Regression analysis method conducted by using IBM SPSS Statistics Ver.28 software with purposive sampling technique. The results of this research shows that Service Quality Elements has a positive and negative correlation also significant and non-significant effect on Customer Satisfaction at BRI Unit Unsrat Manado. Keywords: Service Quality Elements, Customer Satisfaction